The body weight changes and gut merphometry of clarias gariepinus juveniles on feeds supplemented with walnut (Tetracarpidium conophorum) leaf and onions (allium cepa) bulb residues (2012)
This experiment was conducted to evaluate the effects of walnut (T. conophorum) leaf and onion (A. cepa) bulb on the gut morphometry of Clarias gariepinus towards elucidating its mechanism of growth promotion. Twenty Clarias gariepinus juveniles (7.390.29g/ fish) were allocated to nine treatments, with three replicates each. Nine experimental diets were formulated at 40% crude protein representing different level of walnut leaf and onion bulb (0.5%, 1.0%, 1.5% and 2.0%) respectively and the control diet was free from walnut leaf and onion bulb and were fed twice daily at 3 % body weight for 12 weeks. Growth indices like Mean Weight Gain (MWG), Specific Growth Rate (SGR), Feed Intake (FI) and Feed Conversion Ratio (FCR) were measured. Gut morphormetry such as villi length, villi width and cryptal depth were investigated. Data were analyzed using linear regression, descriptive statistics and ANOVA at p= 0.05. Results showed that weight gain and specific growth rate of Clarias gariepinus increased with increasing level of walnut leaf and onion bulb residues. The highest weight gain (53.815.85), specific growth rate (1.090.11), feed conversion ratio (2.160.02) was observed with 1.5% inclusions of walnut leaf residue diets. Although, FCR and SGR were not significantly different (p>0.05) among the treatments, the treated groups had better area of absorption and cryptal depth compared to the control. Treatment with 1.5% inclusion of walnut leaf residue recorded highest villi length and villi width and treatment with 1.5% inclusion of onion bulb recorded highest cryptal depth (30.000.00). These results indicate that using walnut leaf and onion bulb as a supplement in plant –based diets may be useful in improving feed acceptability and growth performance of cultured C. gariepinus fed low cost, plant – based diets and it was concluded that walnut (T. conophorum) leaf at 1.5% inclusion in the diet of Clarias gariepinus improved body weight gain, feed conversion ratio by increasing the absorptive capacity through increased villi length, villi width and cryptal depth